Green Technology and Its Impact on Economic Sustainability after 2020 (قضايا سياسية, 2024)
The research explores the intersection between green technology and economic sustainability, specifically analyzing the impact of green innovations on economic sustainability after 2020. It highlights the significant advancements in green technologies, particularly in renewable energy sources such as solar, wind, and hydropower, along with modern technologies that are reshaping industries and creating new economic opportunities while reducing reliance on fossil fuels.The research concludes that green technologies are crucial for achieving long-term economic sustainability, offering benefits such as increased efficiency, reduced environmental degradation, and the creation of new industries and jobs. However, these benefits are contingent upon strong policy support, investment in innovation, and global cooperation. The transition to a green economy is a complex and multifaceted process that requires collaboration among governments, industries, and consumers.